INFLUENCE OF SOLVENT COMPOSITION ON THE PROCESS OF HYDROGENATION OF VEGETABLE OILS - Suvanova, Fayoza (Innovatsion texnologiyalar, 2024)
The process of hydrogenation of vegetable oils occurs at temperatures above 2000C. In order to reduce the temperature, it is advisable to carry it out in a solvent (miscella). This article presents the results of a study of the chemical composition and physicochemical properties of solvents used in oil extraction production: extraction gasoline and hydrocarbon solvent. The results of a study of the process of hydrogenation of cottonseed oil in solvents showed that the nature of the solvent does not significantly affect the laws of the process itself. The speed and selectivity of the process in the hydrocarbon solvent increased noticeably, which indicates a decrease in the toxicity of the hydrogenation catalyst by organosulfur compounds contained in the solvent in smaller quantities compared to extraction gasoline.